2019
DOI: 10.4049/jimmunol.1900104
|View full text |Cite
|
Sign up to set email alerts
|

Immune Response Resetting in Ongoing Sepsis

Abstract: Cure of severe infections, sepsis, and septic shock with antimicrobial drugs is a challenge because morbidity and mortality in these conditions are essentially caused by improper immune response. We have tested the hypothesis that repeated reactivation of established memory to pathogens may reset unfavorable immune responses. We have chosen for this purpose a highly stringent mouse model of polymicrobial sepsis by cecum ligation and puncture. Five weeks after priming with a diverse Ag pool, high-grade sepsis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 130 publications
1
37
0
Order By: Relevance
“…Ideally, this approach should be combined with other therapeutic strategies directed at reducing the pathogen load. In our earlier work, imipenem had this role (121). Perhaps remdesivir, or any other antiviral drug that proves to be effective, could play this part in the context of SARS-CoV-2 infection.…”
Section: Hypothesismentioning
confidence: 92%
See 4 more Smart Citations
“…Ideally, this approach should be combined with other therapeutic strategies directed at reducing the pathogen load. In our earlier work, imipenem had this role (121). Perhaps remdesivir, or any other antiviral drug that proves to be effective, could play this part in the context of SARS-CoV-2 infection.…”
Section: Hypothesismentioning
confidence: 92%
“…In the case of sepsis, the strong secondary activation and memory response would generate a new hypoinflammatory context that takes over the antipathogen response and is more conducive to disease resolution. Indeed, we have recently demonstrated that repeated reactivation of established T cell memory to a pool of diverse and mostly unrelated pathogens may reset unfavorable immune responses in a mouse model of polymicrobial high-grade sepsis induced by cecum ligation and puncture (121). This off-target revaccination produced .5-fold higher sepsis cure rate when employed in combination with imipenem as compared with the survival achieved with the use of this antibiotic alone.…”
Section: Painful and Inspiring Lessons From Sepsis For Covid-19 Immunmentioning
confidence: 99%
See 3 more Smart Citations